Tracing the evolution of amniote chromosomes - Deakin, Janine E. (Springer Berlin Heidelberg, 2014)
A great deal of diversity in chromosome number and arrangement is observed across the amniote phylogeny. Understanding how this diversity is generated is important for determining the role of chromosomal rearrangements in generating phenotypic variation and speciation. Gaining this understanding is achieved by reconstructing the ancestral genome arrangement based on comparisons of genome organization of extant species. Ancestral karyotypes for several amniote lineages have been reconstructed, mainly from cross-species chromosome painting data. The availability of anchored whole genome sequences for amniote species has increased the evolutionary depth and confidence of ancestral reconstructions from those made solely from chromosome painting data. Nonetheless, there are still several key lineages where the appropriate data required for ancestral reconstructions is lacking. This review highlights the progress that has been made towards understanding the chromosomal changes that have occurred during amniote evolution and the reconstruction of ancestral karyotypes.